Bicyclist Safety Behaviors in an Urban Northeastern, United States City: An Observational Study. Issue 3 (May 2016) - Wolfe, Elizabeth Suzanne; Arabian, Sandra Strack; Salzler, Matthew J.; Bugaev, Nikolay; Rabinovici, Reuven
Abstract : Bicycling is gaining popularity in the United States, and laws and safety recommendations are being established to keep bicyclists safer. To improve road safety for bicyclists, there is a need to characterize their compliance with road laws and safety behaviors. Adult bicyclists were observed at three high-traffic intersections in Boston, MA, with state recommendations of wearing a helmet and riding in a bike lane. State law compliance for displaying reflectors during the day and of a front light and a rear light/reflector at night, obeying traffic signals, and giving pedestrians the right of way was also observed. Variables were compared between personal and shared/rented bicyclists and analyzed by time of day. A total of 1, 685 bicyclists were observed. Because of the speed of the bicyclists and obstructed views, only a sampling of 802 bicyclists was observed for reflectors/front light. Overall, 74% wore a helmet, 49% had reflectors/front lights, 95% rode in bike lanes, 87% obeyed traffic signals, and 99% gave the right of way to pedestrians. Compared with shared bicyclists ( n = 122), personal bicyclists ( n = 1563) had a higher helmet-wearing behaviors (77% vs. 39%, p = .0001). Shared bicyclists had a higher ( p = .0001) compliance with reflectors/lights (100%) than personal bicyclists (39%, n = 265). Boston bicyclists ride in bike lanes, obey traffic signals, give pedestrians the right of way, and wear helmets while having suboptimal compliance with light/reflector use. Educational programs and stricter law enforcement aimed at these safety behaviors should be part of the effort to improve safety for all road users.